Pengaruh Biaya Operasional Pengiriman dan Pendapatan Terhadap Kinerja Keuangan - N, Nurmuthmainna; Idris, Rabihatun; Tangngisalu, Jannati; Ikbal, Muhammad (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This study aims to analyze the influence of delivery operational costs and revenue on the financial performance of PT Sulawesi Mitra Rajawali. The company operates in the logistics and delivery sector in Sulawesi, Indonesia. Financial data from previous years were analyzed to evaluate the impact of delivery operational costs and revenue on the company's financial performance. The research method used is multiple linear regression analysis. The analysis results indicate that delivery operational costs have a significant impact on the company's financial performance, with an increase in operational costs negatively affecting profitability. On the other hand, revenue has a significant positive influence on financial performance, where an increase in revenue enhances the company's profitability. The findings of this research can provide valuable insights for the management of PT Sulawesi Mitra Rajawali in decision-making related to controlling delivery operational costs and increasing revenue to improve the company's financial performance. Additionally, this research can also serve as a reference for similar companies in the logistics and delivery industry facing similar challenges in managing operations and optimizing their revenue.